Stokes’ Problems for an Incompressible Couple Stress Fluid - Devakar, M.; Iyengar, T. K. V. K. V. (Nonlinear Analysis: Modelling and Control, 2008)
Stokes’ first and second problems for an incompressible couple stress fluid are considered under isothermal conditions. The problems are solved through the use of Laplace transform technique. Inversion of the Laplace transform of the velocity component in each case is carried out using a standard numerical approach. Velocity profiles are plotted and studied for different times and different values of couple stress Reynolds number. The results are presented through graphs in each case.